Formation of nano-porous GeOx by de-alloying of an Al–Ge–Mn amorphous alloy. (15th July 2015) - Kim, K.C.; Park, S.H.; Na, M.Y.; Chang, H.J.; Kim, W.T.; Mattern, N.; Eckert, J.; Yokoyama, Y.; Kim, K.B.; Kim, D.H.
Abstract : The present study shows that nanometer-scale amorphous phase separation occurs by spinodal decomposition of the undercooled liquid in a melt-spun Al60 Ge30 Mn10 alloy, although there is no atomic pair with positive enthalpy of mixing. By adopting a proper de-alloying process, an interconnected nano-porous germanium oxide with an amorphous structure is successfully synthesized. The present study shows that nano-porous amorphous germanium oxide can be easily obtained by de-alloying of Al-based amorphous alloys with nm-scale composition fluctuation.